IDENTIFICATION OF CHARCOAL AND AMS RADIOCARBON DATING OF SAMPLES FROM THE FISH WEIR SITE, 49-GUL-380 - Puseman, Kathryn (PaleoResearch Institute) (the Digital Archaeological Record)
Three charcoal samples from the Fish Weir site, 49-GUL-380, were submitted for identification. This site is situated near the Gulkana River in southcentral Alaska and is known ethnographically as the location of the northernmost fishing wier of the Gulkana-Gakona band of the Ahtna (John Jangala, personal communication, September 21, 2010). Samples were recovered from a shallow depression believed to be the floor of a summer dwelling and from levels in Unit 1, including a fire-cracked rock (FCR) locus. The three charcoal samples, as well as a fragment of charred birch bark, were submitted for AMS radiocarbon dating.